Hubungan Mekanisme Koping Terhadap Tingkat Cemas Mahasiswa Fakultas Kedokteran Universitas Muhammadiyah Semarang dalam Penyusunan Skripsi - Ayuningsih, Jihan Ayuningsih; Anggarini, Hesti; Romadhoni, Romadhoni (Universitas Pahlawan Tuanku Tambusai, 2025)
Anxiety is an affective disorder characterized by feelings of fear or deep and ongoing worry. In the context of writing a thesis, various pressures can cause students to feel anxious and experience psychological problems. The many negative impacts caused make anxiety an important thing that must be overcome, therefore self-adjustment to overcome problems is carried out by means of coping mechanisms where each individual has different coping mechanisms. This study aims to determine the relationship between coping mechanisms and the level of anxiety of students of the Faculty of Medicine, Muhammadiyah University of Semarang in writing a thesis. This study is an observational study with a Cross Sectional design. Respondents in this study were students of the Faculty of Medicine, Muhammadiyah University of Semarang who were in the process of writing a thesis. The research instrument was the Brief Cope Scoring questionnaire for coping mechanisms and the Hamilton Rating Scale for Anxiety (HARS) for anxiety levels. The data analysis used was the Spearman Rank test. The results of this study showed that the number of respondents in this study was 39 people. The majority of respondents experienced mild anxiety 94.9%. Statistical test obtained a p-value of 0.000 (<0.05) and a correlation coefficient (r) of 0.548 which indicates the strength of the relationship between variables is moderate with a positive correlation direction. Based on this study, it is concluded that there is a relationship between coping mechanisms and the level of anxiety of students of the Faculty of Medicine, Muhammadiyah University of Semarang in compiling a thesis.